2014
DOI: 10.1007/978-1-4939-1902-4_8
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Staining Methods in Plant Cells

Abstract: Commercially available fluorescent dyes enable the fast and specific visualization of plant vacuoles, allowing for investigation of membrane dynamics and vacuolar biogenesis in living cells. Here, we describe different approaches tinting the tonoplast or the vacuolar lumen with a range of dyes, and illustrate its utilization with established fluorescent-tagged marker lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…This allows us to assess the impact of cell wall acidification before the actual onset of elongation. Using the tonoplast stain MDY-64 or the tonoplast marker line pUBQ10::VAMP711-YFP (Geldner et al, 2009;Löfke et al, 2015;Scheuring et al, 2015), we revealed that cell wall acidification correlated with a dramatic alteration in vacuolar morphology (Fig 2A, C and E), leading to an increased vacuolar occupancy of the cell ( Fig 2B, D and F). Fusicoccin-induced cell wall acidification had an immediate (within 30 min) influence on the vacuolar lumen (Appendix Fig S2A and B), suggesting that cell wall A Representative images and quantification of vacuolar morphology of late meristematic cells.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This allows us to assess the impact of cell wall acidification before the actual onset of elongation. Using the tonoplast stain MDY-64 or the tonoplast marker line pUBQ10::VAMP711-YFP (Geldner et al, 2009;Löfke et al, 2015;Scheuring et al, 2015), we revealed that cell wall acidification correlated with a dramatic alteration in vacuolar morphology (Fig 2A, C and E), leading to an increased vacuolar occupancy of the cell ( Fig 2B, D and F). Fusicoccin-induced cell wall acidification had an immediate (within 30 min) influence on the vacuolar lumen (Appendix Fig S2A and B), suggesting that cell wall A Representative images and quantification of vacuolar morphology of late meristematic cells.…”
Section: Resultsmentioning
confidence: 97%
“…We either directly acidified the rhizosphere (by lowering the pH of the media) or genetically (SAUR19 induction) as well as pharmacologically (fusicoccin treatment) induced the activity of the plasma membrane H + -ATPase (Marre, 1979;Spartz et al, 2014Spartz et al, , 2017. Using the tonoplast stain MDY-64 or the tonoplast marker line pUBQ10::VAMP711-YFP (Geldner et al, 2009;Löfke et al, 2015;Scheuring et al, 2015), we revealed that cell wall acidification correlated with a dramatic alteration in vacuolar morphology ( A Representative images and quantification of vacuolar morphology of late meristematic cells. We quantified the vacuolar morphology, depicting the dimension of the biggest luminal vacuolar structure Scheuring et al, 2016), in root epidermal cells of the late meristematic zone.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular trafficking of flg22 and the identity of fluorescently labeled compartments was evaluated by colocalization with dyes staining plasma membrane, endocytic vesicles and MVBs (FM4-64) (Bolte et al , 2004; van Gisbergen et al , 2008) or prevacuolar compartments/vacuoles (BCECF) (Brauer et al , 1995; Scheuring et al , 2015). FM4-64 has previously been used to confirm endocytosis of activated FLS2 (Beck et al , 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Whenever vacuolar morphology was analyzed, roots were mounted in PI solution (0.02 mg/mL) to counterstain cell walls. MDY-64, FM4-64, and BCECF staining was performed as described previously (32). Z-stacks were recorded with a step size of 420 nm, resulting in 25-35 Z-stack images per cell.…”
Section: Significancementioning
confidence: 99%